Will biologists become computer scientists?: A truly interdisciplinary effort by computer scientists and biologists to understand how cells process information may yield new insights for both fields. (30th July 2018) - Condon, Anne; Kirchner, Hélène; Larivière, Damien; Marshall, Wallace; Noireaux, Vincent; Tlusty, Tsvi; Fourmentin, Eric
Abstract : Though made from different materials, cells and computers are both information‐processing machines. Computer science could help biologists to better understand how cells sense, process and adapt to cues from their environment.